2017
DOI: 10.1186/s40880-017-0242-3
|View full text |Cite
|
Sign up to set email alerts
|

Medical expenditure for esophageal cancer in China: a 10-year multicenter retrospective survey (2002–2011)

Abstract: BackgroundEsophageal cancer is associated with substantial disease burden in China, and data on the economic burden are fundamental for setting priorities in cancer interventions. The medical expenditure for the diagnosis and treatment of esophageal cancer in China has not been fully quantified. This study aimed to examine the medical expenditure of Chinese patients with esophageal cancer and the associated trends.MethodsFrom 2012 to 2014, a hospital-based multicenter retrospective survey was conducted in 37 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 15 publications
1
27
0
1
Order By: Relevance
“…Esophageal cancer is one of the most common malignant tumors with 400,156 deaths worldwide in 2012 and it exhibits a high incidence in China (1). Of those patients with esophageal cancer, ~90% patients are diagnosed with esophageal squamous cell carcinoma (ESCC) (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal cancer is one of the most common malignant tumors with 400,156 deaths worldwide in 2012 and it exhibits a high incidence in China (1). Of those patients with esophageal cancer, ~90% patients are diagnosed with esophageal squamous cell carcinoma (ESCC) (1).…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer is one of the most common malignant tumors with 400,156 deaths worldwide in 2012 and it exhibits a high incidence in China (1). Of those patients with esophageal cancer, ~90% patients are diagnosed with esophageal squamous cell carcinoma (ESCC) (1). However, a lack of progress in chemotherapy and radiotherapy has resulted in little improvement of ESCC treatment, leading to a 5-year survival rate of 15-25% (2).…”
Section: Introductionmentioning
confidence: 99%
“…Although economic burden of cancer has been assessed in many countries, such as the United States, the United Kingdom, India, and across the European Union, the current evidence on the cost of cancer treatment in China is limited. So far, studies on cancer in China mostly focus on the incidence and prevalence of cancer, or treatment cost of specific cancer types such as stomach cancer, esophageal cancer, and liver cancer . There are few studies providing valuable evidence for the economic burden of all cancer types.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in China tended to categorize age into four or more groups and found no clear association between medical expenditure and age group ( 4 , 6 ). In this study, we categorized age into two groups and found that for both cancers, non-elderly patients were associated with lower CPH and more frequent hospitalization ( Supplementary Table S5 ) in urban and rural areas whereas in Japan, greater medical costs were associated with elderly patients ( 11 ).…”
Section: Discussionmentioning
confidence: 89%
“…Compared with the abundant evidence on the epidemiological burden of stomach and esophageal cancer, only a few researches had been done concerning the economic burden of them at patient level in China ( 4 - 6 ). Moreover, these studies were carried out in either one area (county, province) ( 5 , 6 ) or only urban areas ( 4 ). To date, in-depth studies on the cost of illness of stomach or esophageal cancer at patient level have been conducted mainly in developed countries ( 7 - 12 ).…”
Section: Introductionmentioning
confidence: 99%